1998
DOI: 10.1210/jcem.83.8.5059
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of theMEN1Gene in Multiple Endocrine Neoplasia Type 1, Familial Acromegaly and Familial Isolated Hyperparathyroidism1

Abstract: Multiple endocrine neoplasia type 1 (MEN 1) is an autosomal dominant disease characterized by neoplasia of the parathyroid glands, the endocrine pancreas, and the anterior pituitary gland. In addition, families with isolated endocrine neoplasia, notably familial isolated hyperparathyroidism (FIHP) and familial acromegaly, have also been reported. However, whether these families constitute MEN 1 variants or separate entities remains speculative as the genetic bases for these diseases are unclear. The gene for M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…More than 300 different MEN1 germline mutations have now be identified in several independent national studies based on large series of MEN1 patients [22, 23, 24, 25, 26, 27]. Figure 1 shows the spectrum of most MEN1 mutations identified in France and recurrent mutations described by other groups.…”
Section: Basic Pathways Related To Genetic Predispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 300 different MEN1 germline mutations have now be identified in several independent national studies based on large series of MEN1 patients [22, 23, 24, 25, 26, 27]. Figure 1 shows the spectrum of most MEN1 mutations identified in France and recurrent mutations described by other groups.…”
Section: Basic Pathways Related To Genetic Predispositionmentioning
confidence: 99%
“…Intronic and splice-junction mutations were reported in a few families and some of them were shown to alter RNA splicing with an abnormal exon skipping or intronic retention [28, 29]. Most mutations occurred once, while some of them were observed twice or more in apparently unrelated families [22, 23, 24, 25, 26, 27]. Haplotype analysis with 11q13 polymorphic markers demonstrated that most recurrent mutations were not related to a founder effect assessing the data from two independent linkage disequilibrium studies performed before the MEN1 gene was cloned [30].…”
Section: Basic Pathways Related To Genetic Predispositionmentioning
confidence: 99%
“…The position of the epitope recognized by the antibody M1C2 is underlined. Below are indicated the position of constitutional (c) and somatic (s) missense mutations and single amino acid deletions detected in MEN 1 patients Agarwal et al, 1997;Bassett et al, 1998;Teh et al, 1998) and sporadic parathyroid Farnebo et al, 1998), pancreatic-duodenal (Toilat et al, 1997;Zhuang et al, 1997b) and pituitary tumours. For some amino acids more than one mutation was found, and the number is given in parenthesis (2 or 3) Uppercase and lowercase letters denote exonic and intronic sequences, respectively.…”
Section: Rna and Protein Expressionmentioning
confidence: 99%
“…The MEN1 gene was localized to 11q13 (Larsson et al, 1988) and later identi®ed by positional cloning . Mutation analysis of the MEN1 gene has so far revealed more than 200 MEN1 index cases with unique heterozygous germ-line mutations Bassett et al, 1998;Teh et al, 1998;Giraud et al, 1998;Poncin et al, 1999;Mutch et al, 1999). Analogous somatic mutations in the MEN1 gene are a major contributor to sporadic tumors: parathyroid adenomas, lung carcinoids, gastrinomas, insulinomas, and angio®bromas Debelenko et al, 1997;Zhuang et al, 1997;Boni et al, 1998).…”
Section: Introductionmentioning
confidence: 99%